Comparative Studies on Phospholipase A2 as a Marker for Gut Microbiota- liver-brain Axis in a rodent Model of Autism - Al-Dbass, Abeer; Bacha, Abir B.; Moubayed, Nadine M.S.; Bhat, Ramesa Shafi; Al-Mutairi, Manar; Alnakhli, Osima M.; Al-Mrshoud, Majidh; Alfawaz, Hanan; Daghestani, Maha; El-Ansary, Afaf (Current Proteomics, 2021)
Background: Lipid homeostasis and gut flora can be related to many metabolic diseases, especially autism. Lipid metabolism in the brain can control neuronal structure and function and can also take part in signal transduction pathways to control metabolism in peripheral tissues, especially in the liver. Impaired phospholipid metabolism promotes oxidative stress and neuroinflammation and is, therefore, directly related to autism. Objective: The effect of propionic acid (PPA) toxicity on lipid homeostasis in the gut-liver-brain axis was evaluated to understand their inter-connection. Cytosolic phospholipase A2 (cPLA2) concentration and activity was measured in autistic model and protective role of omega-3 (ω-3) and vitamin B12 was evaluated. Methods: Animals were divided into five groups: Group I (control group); Group II (autistic model treated with neurotoxic dose of PPA); Group III (treated with vitamin B12 (16.7 mg/kg/day) for 30 days post PPA treatment); Group IV (treated with ω-3 (200 mg/kg body weight/day) for 30 days post PPA treatment; Group V (combined dose of ω-3 and Vitamin B12, for 30 days post PPA treatment). Phospholipase A2 activity and protein expression level in the liver homogenate of all the groups was analyzed by western blotting and was compared to brain cPLA2. Results: PPA increased the levels of liver and brain cPLA2. However, independent or combined treatment with ω-3 and vitamin B12 was effective in neutralizing its effect. Moreover, PPA-induced dysbiosis, which was ameliorated with the above treatments. Conclusion : This study showed the role of cPLA2 as a lipid metabolism marker, related to PPA-induced inflammation through a highly interactive gut-liver-brain axis.
Keywords: gut microbiota